Functional genomic analysis of Bacillus cereus BC4 strain for chromium remediation in contaminated soil - Zhiyi Liu; Yubing Cai; Xu Chen; Yan Cang; Jialiang Yu; Muhammad Shaaban; Yajun Cai; Qi-an Peng (Current Research in Microbial Sciences)
Soil provides a habitat for microorganisms that can mitigate metal contamination. This study presents Bacillus cereus BC4 strain, which shows significant potential for metal pollution remediation. This bacterium achieved a 98.6 % reduction in Chromium (VI) concentrations from 300 mg/L to negligible levels under specific conditions (pH 8, 37 °C, and 120 rpm agitation) in LB medium. The complete genome of Bacillus cereus BC4 was sequenced using Oxford Nanopore Technology, revealing a circular chromosome and a plasmid with a total of 5537,675 base pairs and a G + C content of 35.44 %. Fourteen genes critical for Cr metabolism were identified. qRT-PCR demonstrated that under low Cr(VI) stress, two genes, chrA and nitR1, were up-regulated, indicating their role in Cr resistance. The genome revealed gene clusters essential for resilience against various metals, including chromium, arsenic, copper, manganese, and cadmium, as well as for synthesizing secondary metabolites crucial for survival and adaptation. Additionally, genes associated with biopolymer synthesis were identified, emphasizing the organism's diverse genetic capabilities. This genomic study led to the submission of the complete genome to GenBank (CP101135), enhancing the understanding and potential of Bacillus cereus BC4 in chromium remediation and environmental restoration.